2006
DOI: 10.1177/147323000603400107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selective Brain Cooling in Patients with Severe Traumatic Brain Injury: A Preliminary Study

Abstract: We prospectively investigated noninvasive selective brain cooling (SBC) in patients with severe traumatic brain injury.Sixty-six in-patients were randomized into three groups. In one group, brain temperature was maintained at 33 -35°C by cooling the head and neck (SBC); in a second group, mild systemic hypothermia (MSH; rectal temperature 33 -35°C) was produced with a cooling blanket; and a control group was not exposed to hypothermia. Natural rewarming began after 3 days. Mean intracranial pressure 24, 48 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 19 publications
(21 reference statements)
1
68
0
Order By: Relevance
“…Finally, patients who received systemic cooling (full body) were compared with those who received selective brain cooling (head only) and normothermia. Pneumonia rates were lowest and 2-year GOS scores were highest in patients who received selective cooling 64 . Although the results of these studies are promising, the findings are tempered by contradictory findings from similar studies conducted in other countries.…”
Section: Chinamentioning
confidence: 90%
“…Finally, patients who received systemic cooling (full body) were compared with those who received selective brain cooling (head only) and normothermia. Pneumonia rates were lowest and 2-year GOS scores were highest in patients who received selective cooling 64 . Although the results of these studies are promising, the findings are tempered by contradictory findings from similar studies conducted in other countries.…”
Section: Chinamentioning
confidence: 90%
“…The idea to develop new devices for selective neuroprotective cooling of the brain parenchyma has already been published [12,[26][27][28][29][30][31][32]. In each of the studies, the device became more specific and smaller [33].…”
Section: Discussionmentioning
confidence: 99%
“…No difference in the development of pneumonia between control and hypothermia groups was reported in 5 trials, [26][27][28]32 and sepsis or pneumonia were more commonly reported in hypothermic patients in 2 trials. 17,31 No study reported an increase in hemorrhagic complications with hypothermia (either intracranial or systemic), though 4 reported thrombocytopenia 19,27,31,33 and 3 reported slight prolongations in the partial thromboplastin time or prothrombin time. 17,19,26 Although hypokalemia was the most common electrolyte abnormality, reported in 6 trials, 8,17,19,25,26,28 it was treated without serious sequelae in all studies.…”
Section: Prophylactic Hypothermia For Traumatic Brain Injurymentioning
confidence: 99%